Simulation of Parameters Influencing the Electric Vehicle Range - Kucera, Lubos; Gajdac, Igor; Mruzek, Martin (Communications - Scientific letters of the University of Zilina, 2016)
Increasing the range of electric vehicles is crucial for electromobility expansion. Using the simulation it is possible to identify the parameters that have a significant impact on the electric vehicle range. Therefore, the analysis of parameters influencing the range was created. Simulation was based on real driving cycles for better accuracy.